ANALISIS FAKTOR YANG MEMPENGARUHI HARGA DAN INTEGRASI HARGA OLEIN - Desak Putu Ristami Paramita; Nunung Nuryartono; Noer Azam Achsani (IPB University, 2015)
Olein production increased by 107.5 percent from 2002 to 2013. There was a change in consumption patterns where the consumption of olein intended for export has risen from only 39 percent in 2002 to 65 percent in 2013. In the beginning of 2008, olein prices increased due to the global financial crisis. In the end of 2008, olein prices decreased but since then olein prices fluctuations until the end of 2014. Many factors affecting the price fluctuations such as macroeconomic and microeconomic variables. Commodity market participants need to take action in response to price fluctuations by participating in commodity futures trading. Olein futures trading commodity in Indonesia is not well developed. This is indicated by small volumes of the transaction of olein futures contracts in Indonesia Commodity and Derivatives Exchange (ICDX) causing market participants to not using ICDX futures prices as a reference. The participants actually use the price of the Rotterdam exchange for their transactions of buying and selling. Therefore, this study aims to analyze factors influencing olein prices and analyze olein prices integration by using Vector Error Correction Model (VECM) method. Results showed that exchange rates, interest rates, money supply, CPO prices, and Indonesia's GDP affect olein prices. In addition, there is an integration between the physical prices, futures prices, and world reference prices in the long term. Key words : Factors Affecting Price, Olein, Price Integration, VECM